2016
DOI: 10.1002/hed.24377
|View full text |Cite
|
Sign up to set email alerts
|

Successful detection of a minute tonsillar cancer lesion on transoral examination with narrow band imaging: A report of 2 cases

Abstract: We detected a small primary lesion in the palatine tonsil through transoral examination with NBI, which is a simple and noninvasive method. This approach may be useful to detect subtle lesions, especially in patients with human papillomavirus (HPV)-related tonsillar cancer. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2421-E2424, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…They refined the staging system into three recursive partitioning analysis (RPA) groups: RPA-I (T1-T3, N0-2b), RPA-II (T1-T3, N2c), and RPA-III (T4 or N3); this is a more accurate prognosis prediction system. [56]. Tumor was almost covered by normal mucosa (arrowheads).…”
Section: Clinical Staging For Opcmentioning
confidence: 97%
See 3 more Smart Citations
“…They refined the staging system into three recursive partitioning analysis (RPA) groups: RPA-I (T1-T3, N0-2b), RPA-II (T1-T3, N2c), and RPA-III (T4 or N3); this is a more accurate prognosis prediction system. [56]. Tumor was almost covered by normal mucosa (arrowheads).…”
Section: Clinical Staging For Opcmentioning
confidence: 97%
“…Transoral endoscopic examination with narrow-band imaging is thought to be effective to detect a small lesion (Fig. 2b) [56].Conversely, classical HPV-unrelated OPC arises from the surface area of the oropharynx, which is caused by tobacco smoking and alcohol exposure, and may therefore be more easily observed or diagnosed.…”
Section: Clinical Features Of Hpc-related Opsccmentioning
confidence: 98%
See 2 more Smart Citations
“…Ebisumoto et al [56] have reported their successful experience to detect minute p16-positive tonsillar cancer lesions on transoral examination with narrow band imaging (NBI). This imaging technique works by filtering white light into specific light wavelengths that are absorbed by haemoglobin and consequently enhances the visibility of the mucosal superficial vasculature [57].…”
Section: Identification Of Lesions In Individuals With a Positive Scrmentioning
confidence: 99%